Memorable Encounters? Own and Neighbours' Experience with IMF Conditionality and IMF Stigma - Irina Andone; Beatrice D. Scheubel (Center for Economic Studies and ifo Institute (CESifo), 2017)
While the consequences and effectiveness of IMF conditionality have long been the focus of research, the possible negative impact of IMF conditionality on countries' willingness to ask for an IMF programme - often termed `IMF stigma' - has recently received attention particularly from policy circles. In this paper we investigate how countries' past experience with the IMF affects their likelihood of entering an IMF arrangement again. To also allow for such learning for countries which never had an IMF programme, we include neighbours' past IMF conditionality. Our results indicate strong learning from own experience, but hardly any learning from neighbours, except for ASEAN countries. We conjecture that the stigma associated with IMF conditionality may exist for individual country cases, but that a more general `IMF stigma' cannot be related to observing how the IMF treats peers.
Keywords: F33; F53; F55; H87; 330; financial arrangements; reserves; IMF MONA; crisis resolution